Preferential Gs protein coupling of the galanin Gal1 receptor in the µ-opioid-Gal1 receptor heterotetramer. (August 2022) - De Oliveira, Paulo A.; Moreno, Estefanía; Casajuana-Martin, Nil; Casadó-Anguera, Verònica; Cai, Ning-Sheng; Camacho-Hernandez, Gisela Andrea; Zhu, Hu; Bonifazi, Alessandro; Hall, Matthew D.; Weinshenker, David; Newman, Amy Hauck; Logothetis, Diomedes E.; et al.
Abstract: Recent studies have proposed that heteromers of µ-opioid receptors (MORs) and galanin Gal1 receptors (Gal1 Rs) localized in the mesencephalon mediate the dopaminergic effects of opioids. The present study reports converging evidence, using a peptide-interfering approach combined with biophysical and biochemical techniques, including total internal reflection fluorescence microscopy, for a predominant homodimeric structure of MOR and Gal1 R when expressed individually, and for their preference to form functional heterotetramers when co-expressed. Results show that a heteromerization-dependent change in the Gal1 R homodimeric interface leads to a switch in G-protein coupling from inhibitory Gi to stimulatory Gs proteins. The MOR-Gal1 R heterotetramer, which is thus bound to Gs via the Gal1 R homodimer and Gi via the MOR homodimer, provides the framework for a canonical Gs-Gi antagonist interaction at the adenylyl cyclase level. These novel results shed light on the intense debate about the oligomeric quaternary structure of G protein-coupled receptors, their predilection for heteromer formation, and the resulting functional significance. Graphical Abstract: ga1